Economic Literacy Levels of Public Officers in Turkey - Rüştü Yayar (Corresponding author) (Pakistan Journal of Commerce and Social Sciences, 2017)
Behaviors of consumers and producers become complex and interdependent in accordance with the developments in the world. This development increases the importance of economic knowledge and it becomes more and more important for the individuals and societies to adapt themselves to this development. Economic literacy is of high importance not only for specific social groups but also all the individuals. However; economic knowledge of the public officers who are in a specific level of income, expense and education within Turkish economy as well as their ability of applying this knowledge on their daily lives and their prospective economic planning as being conscious individuals are of high importance. Increase in economic literacy of the individuals not only affects the individuals but also contributes to the society and country. This study aims at determining and evaluating economic literacy levels of the public officers. It includes public officers working in Tokat city center. Research data has been obtained from 397 participants randomly selected as a result of face to face interviews. Factor analysis, independent sample t test and one-way analysis of variance have been applied in the research. It has been determined that averages regarding sub-dimensions of economic literacy of the participants vary depending on gender, age, occupation and income. Economic literacy levels of the public officers have been found high. It is thought the study will be beneficial to politicians, academicians and all decision-makers.